Modified MAX Phase Synthesis for Environmentally Stable and Highly Conductive Ti3C2 MXene - Mathis, Tyler S; Maleski, Kathleen; Goad, Adam; Sarycheva, Asia; Anayee, Mark; Foucher, Alexandre C; Hantanasirisakul, Kanit; Shuck, Christopher E; Stach, Eric A; Gogotsi, Yury (ACS nano, 2021)
One of the primary factors limiting further research and commercial use of the two-dimensional (2D) titanium carbide MXene Ti3C2, as well as MXenes in general, is the rate at which freshly made samples oxidize and degrade when stored as aqueous suspensions. Here, we show that including excess aluminum during synthesis of the Ti3AlC2 MAX phase precursor leads to Ti3AlC2 grains with improved crystallinity and carbon stoichiometry (termed Al–Ti3AlC2). MXene nanosheets (Al–Ti3C2) produced from this precursor are of higher quality, as evidenced by their increased resistance to oxidation and an increase in their electronic conductivity up to 20 000 S/cm. Aqueous suspensions of stoichiometric single- to few-layer Al–Ti3C2 flakes produced from the modified Al–Ti3AlC2 have a shelf life of over ten months, compared to 1 to 2 weeks for previously published Ti3C2, even when stored in ambient conditions. Freestanding films made from Al–Ti3C2 suspensions stored for ten months show minimal decreases in electrical conductivity and negligible oxidation. Furthermore, oxidation of the improved Al–Ti3C2 in air initiates at temperatures that are 100–150 °C higher than that of conventional Ti3C2. The observed improvements in both the shelf life and properties of Al–Ti3C2 will facilitate the widespread use of this material.